INTERPRETASI SIKAP MAHASISWA AKUNTANSI TERHADAP UNDANG-UNDANG AKUNTAN PUBLIK GUNA PERENCANAAN KARIR DITINJAU DARI SOCIAL COGNITIVE CAREER THEORY - Zulfikar Zulfikar; Eko Adi Widyanto (Jurnal Eksis, 2016)
Explanation of Article 6, paragraph 1 letter a public accountant at the Law which reads "who can participate in education the public accounting profession is someone who has a minimum of a bachelor of education 1 (S-1), diploma IV ( D-IV), or equivalent" this being debated among students because of the accounting profession through education can come from the accounting and non-accounting majors. This study uses a qualitative method with a phenomenological approach and Social Cognitive Carrer Theory analysis (SCCT) with self efficacy, outcome expectations, and personal goals to describe the perceptions, student motivation and optimism to become a public accountant. The study states that the student is issued perceptions are negative and positive. Accounting student motivation increase with the implementation of this Act as a public accountant will be increasingly shown itself to be capable of competing public accountants, and optimism students to become CPAs higher because students believe knowledge they gained at D-IV majoring in managerial accounting basis is strong optimism. Keywords: CPA Law, Carrer Planning, SCCT